2013
DOI: 10.4103/0973-029x.110685
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of plasma lipids and its significance on histopathological grades in oral cancer: Prognostic significance an original research

Abstract: Background Objectives:Alterations in the lipid profile have long been associated with various cancers because lipids play a key role in maintenance of cell integrity. This study was to estimate the plasma lipid levels in patients with oral cancer and to correlate the values with the histopathological grades.Materials and Methods:The study group included 50 patients with oral cancer aged between 20 and 60 years who had visited the Department of Oral Medicine and Radiology during the period of September 2005 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
11
2
Order By: Relevance
“…TG and LDL showed no significant changes. The results obtained in our study are on par with the results of Jyothi Chawda et al, 7 Sherubin EJ et al, 6 Patel PS et al, 10 Mehrotra R et al, 11 Lohe V et al 12 and Nayak P et al 13 and disagreed with the results of Goyal S et al 5 Our results add to the evidence of inverse relationship between lower serum lipid profile in oral cancer and potentially malignant disorders. Although the role of tobacco has been established as an etiological factor for oral cancer and potentially malignant disorders, it may have an indirect and overall significant association with serum lipid profile.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…TG and LDL showed no significant changes. The results obtained in our study are on par with the results of Jyothi Chawda et al, 7 Sherubin EJ et al, 6 Patel PS et al, 10 Mehrotra R et al, 11 Lohe V et al 12 and Nayak P et al 13 and disagreed with the results of Goyal S et al 5 Our results add to the evidence of inverse relationship between lower serum lipid profile in oral cancer and potentially malignant disorders. Although the role of tobacco has been established as an etiological factor for oral cancer and potentially malignant disorders, it may have an indirect and overall significant association with serum lipid profile.…”
Section: Discussioncontrasting
confidence: 56%
“…The enzyme fatty acid synthase and its activity is highly elevated in biosynthetically altered anaplastic cells of poorly differentiated lesions as compared to moderate and well differentiated lesions. 6 However in contrary to afore mentioned statement, we observed the mean serum lipid parameters TC, TG, HDL, LDL, VLDL, showed no significant p value according to degree of differentiation. Similar findings were also obtained in the studies by Jyothi Chawda et al, 7 Kumar P et al 8 and Anuradha et al 9 In the present study, the serum lipid profile parameters like TC, HDL and VLDL showed lower values in PMD and OC groups when compared to control group.…”
Section: Discussioncontrasting
confidence: 54%
“…40,41 Sherubin et al observed a significant decrease of all lipid levels in patients with oral malignancy. 42 Alexopolus et al have found non-significant difference in serum triglyceride levels between controls and patients. 13 The results are strengthen by the present study which also shows lower levels of serum levels of total cholesterol, Triglycerides, HDL, VLDL, LDL in oral cancer and precancerous lesion patients.…”
Section: Discussionmentioning
confidence: 95%
“…ACAT catalyses the reaction of free cholesterol to esterified cholesterol. It has therefore been hypothesised that lower cholesterol levels in patients with advanced disease may be due to its increased storage in tumour cells and its utilisation for new membrane biosynthesis . It is unknown whether serum cholesterol can be used as a surrogate for tumour cholesterol and whether these serum cholesterol levels pre‐existed or are a consequence of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Serum cholesterol is another possible surrogate biomarker of lipid metabolism that is broadly available and routinely assessed in many patients. Although widely used to predict outcomes of patients with coronary heart disease, there are few studies that focus on its role as a prognostic marker in cancer . Ohno et al.…”
Section: Introductionmentioning
confidence: 99%